Analysis of the mechanical anisotropy of stereolithographic 3D printed polymer composites. Issue 1 (31st December 2022) - Stögerer, Johannes; Baumgartner, Sonja; Rath, Thaddäa; Stampfl, Jürgen
Abstract: 3D printing is a manufacturing technique based on the structuring of parts layer by layer. This principle yields a specific printing direction, that is the spatial orientation of the produced layers. Thus, potential anisotropy arising from the printing direction is a major concern in 3D printing. The mechanical properties of a biocompatible resin mainly consisting of methacrylates and tricalcium phosphate particles is examined. Various tests are conducted to examine the mechanical anisotropy of testing samples manufactured with a 3D printer based on stereolithography. A digital light processing unit (λ = 375 nm) is utilized to produce test samples in three orthogonal directions. Bending behaviour, fracture toughness, and hardness are measured. Furthermore, light microscopy is utilized to assess the properties of the fractured samples qualitatively. Assessed values are in agreement with comparable materials and show no statistically significant ( p  = 0.095) evidence of anisotropic behaviour. Sample orientation has no impact on the mechanical properties of the produced parts. Thus, production time and capabilities can be optimized by varying and combining sample orientation without changing the mechanical performance of the engineered parts significantly.